2010
DOI: 10.1056/nejmoa0911486
|View full text |Cite
|
Sign up to set email alerts
|

Maternal or Infant Antiretroviral Drugs to Reduce HIV-1 Transmission

Abstract: Background We evaluated the efficacy of a maternal triple-drug antiretroviral regimen or infant nevirapine prophylaxis for 28 weeks during breast-feeding to reduce postnatal transmission of human immunodeficiency virus type 1 (HIV-1) in Malawi. Methods We randomly assigned 2369 HIV-1–positive, breast-feeding mothers with a CD4+ lymphocyte count of at least 250 cells per cubic millimeter and their infants to receive a maternal antiretroviral regimen, infant nevirapine, or no extended postnatal antiretroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
228
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 386 publications
(235 citation statements)
references
References 19 publications
6
228
1
Order By: Relevance
“…This study provided a unique opportunity to investigate humoral correlates of reduced postnatal mother-to-child transmission risk in the absence of postnatal antiretroviral therapy (20). Although no statistically significant associations were identified in the primary logistic regression models after correction for multiple comparisons, in subsequent exploratory analysis, the breast milk IgA responses against B.con env03 gp140 Env were associated with reduced HIV-1 postnatal transmission risk by two independent but related measures: total IgA binding by single-antigen ELISA and SIgA binding by BAMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provided a unique opportunity to investigate humoral correlates of reduced postnatal mother-to-child transmission risk in the absence of postnatal antiretroviral therapy (20). Although no statistically significant associations were identified in the primary logistic regression models after correction for multiple comparisons, in subsequent exploratory analysis, the breast milk IgA responses against B.con env03 gp140 Env were associated with reduced HIV-1 postnatal transmission risk by two independent but related measures: total IgA binding by single-antigen ELISA and SIgA binding by BAMA.…”
Section: Discussionmentioning
confidence: 99%
“…This study enrolled antiretroviral-naive, HIV-1-infected pregnant women in Malawi with CD4 ϩ T cell counts above 200 cells/l (250 cells/l after 24 July 24 2006) from 2004 to 2009. All mothers and infants in the control arm received single-dose nevirapine at onset of labor (postpartum for infants), followed by 7 days of zidovudine/lamivudine therapy (20). Mothers who transmitted HIV-1 to their infants during breastfeeding (n ϭ 22) were included in the current study and matched in a near 1:3 ratio with nontransmitting mothers (n ϭ 65) for postpartum visit and the closest peripheral CD4…”
Section: Methodsmentioning
confidence: 99%
“…The BAN study was a randomized controlled clinical trial that evaluated, in a factorial design, the safety and efficacy of (i) antiretroviral prophylaxis (a maternal triple-drug antiretroviral regimen versus infant daily nevirapine administered during 28 weeks of breastfeeding versus a control arm of only 1 week of antiretroviral prophylaxis after delivery) and (ii) a maternal nutritional supplement during breastfeeding in reducing postnatal mother-to-child HIV transmission and in enhancing maternal health during breastfeeding (19). The study randomized and followed 2,369 mother-infant pairs between 2004 and 2010 in Lilongwe, Malawi; enrolled infants had to have a birth weight of at least 2,000 g and be HIV uninfected by 2 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Given the presence of maternal transplacentally acquired antibody in the infant and the high prevalence of CMV immunity among women in resource-limited settings, antibody avidity was used as a tool to decipher the time of primary CMV infection in the infants. We used samples collected and stored from infants enrolled in the Breastfeeding, Antiretrovirals and Nutrition (BAN) study (19), who breastfed for 28 weeks and were followed for their first 48 weeks of life in Lilongwe, Malawi.…”
mentioning
confidence: 99%
“…These studies demonstrated significant reduction in the risk of motherto-child transmission of HIV by administering ARV medications to the mother or the infant during the breastfeeding period (Chasela et al, 2010). We have found no studies specifically undertaken to make replacement feeding safer for infants unable to breast-feed, whether HIV exposed or unexposed.…”
mentioning
confidence: 99%